REVAMPING TRADITION WITH TECH: GUIDING INNOVATION IN ZAKAT FOR SOCIAL GOOD - Ickhsanto Wahyudi; Euis Amalia; Rini Rini (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
As a pillar of Islam, zakat holds profound meaning and socioeconomic significance. However, oversight deficiencies have constrained its capacity for poverty alleviation. This paper explores emerging technologies - including blockchain, artificial intelligence, and mobile platforms - to strengthen zakat management. Through a qualitative literature review, we examine the digital transformation of zakat systems. We argue for cautious technology adoption to enhance transparency, efficiency, and inclusivity while aligning with Islamic ethics. Guiding principles grounded in maqasid al-shariah are offered, emphasizing human discretion and oversight. While risks around exclusion, security, and algorithmic bias necessitate vigilance, thoughtfully implemented technology can optimize zakat distribution and amplify impact. By leveraging innovation to uphold foundational values, zakat can fulfil its noble obligations of uplifting communities and promoting social justice.